Strategi Mata Pelajaran Agama Islam Dalam Mengatasi Rendahnya Minat Ibadah Kolektif Siswa di SMA Harapan Mekar - Chairani C (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
As is well known, the implementation of collective worship in the school environment is still relatively minimal, especially in public schools such as Senior High Schools (SMA), compared to State Islamic Senior High Schools (MAN) which have a stronger religious content in their curriculum. This difference in institutional background also influences the extent to which interest in worship can be embedded in students' daily lives. Therefore, this study aims to determine the strategies of Islamic religious education teachers in motivating students to carry out worship at Harapan Mekar High School, Medan. The type of research used is qualitative research using a descriptive approach. The results of this study, Islamic Religious Education teachers found strategies that can increase students' interest in worship in the school environment. The main strategies identified include reminding students about prayer times, providing examples of good behavior, and providing encouragement and support. Supporting factors include a conducive environment and collaboration between teachers and students, while inhibiting factors consist of individual busyness and peer influence.